1996
DOI: 10.1016/0735-1097(95)00591-9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric use of intravenous amiodarone: Efficacy and safety in critically III patients from a multicenter protocol

Abstract: Intravenous amiodarone is safe and effective in most young patients with critical tachyarrhythmia. Intravenous amiodarone can be lifesaving, particularly for postoperative junctional ectopic tachycardia, when standard therapy is ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(16 citation statements)
references
References 13 publications
0
12
0
4
Order By: Relevance
“…In 4 small LOE 4 pediatric case series 298,299,314,315 amiodarone was effective in the management of VT. One prospective randomized multicenter safety and efficacy LOE 2 trial evaluating amiodarone for the treatment of pediatric tachyarrhythmias 316 found that 71% of children treated with amiodarone experienced cardiovascular side effects. Both efficacy and adverse events were dose-related.…”
Section: Arrhythmia Therapypeds-030mentioning
confidence: 94%
See 2 more Smart Citations
“…In 4 small LOE 4 pediatric case series 298,299,314,315 amiodarone was effective in the management of VT. One prospective randomized multicenter safety and efficacy LOE 2 trial evaluating amiodarone for the treatment of pediatric tachyarrhythmias 316 found that 71% of children treated with amiodarone experienced cardiovascular side effects. Both efficacy and adverse events were dose-related.…”
Section: Arrhythmia Therapypeds-030mentioning
confidence: 94%
“…Evidence from 2 LOE 5 case series in children 298,299 supported the effectiveness of amiodarone for the treatment and acute conversion of life-threatening (non-arrest) ventricular arrhythmias. There are no pediatric data investigating the efficacy of lidocaine for shock refractory VF/ pulseless VT.…”
Section: Defibrillationmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence from 2 LOE 5 case series in children 298,299 supported the effectiveness of amiodarone for the treatment and acute conversion of life-threatening (nonarrest) ventricular arrhythmias. There are no pediatric data investigating the efficacy of lidocaine for shock refractory VF/pulseless VT.…”
Section: Defibrillationmentioning
confidence: 97%
“…Experts at the 2005 Consensus Conference reviewed the available evidence on use of the tracheal tube and LMA in infants and children. [59] There were no data on the use of the Combitube in this age group.…”
Section: Initial Steps Of Cprmentioning
confidence: 99%